Air entrainment in fresh concrete and its effects on hardened concrete-a review. (8th March 2021) - Shah, Hammad Ahmed; Yuan, Qiang; Zuo, Shenghao
Highlights: Effects of raw materials, processing factors and environment on air entrainment in fresh concrete are reviewed. The testing methods of air void system in concrete at fresh and hardened states are summarized. Effects of air entrainment on properties of concrete at fresh and hardened states are reviewed. Abstract: The presence of the stable and adequate air-void system in fresh and hardened concretes are crucial to many properties, such as resistance against freeze and thaw cycle, workability/rheology, pumpability, strength, and fire resistance of concrete. This paper presents a critical review of the air-void system in fresh and hardened concretes and its effects on various properties. The air entrainment mechanisms and testing methods for air void system were first reviewed. Although the air void system can be measured by different methods, the measurement of the air void system in fresh concrete is still challenging. The influence of air void parameters on the workability and rheology of concrete was then discussed. In the hardened state, the effect of air entrainment on compressive strength, freeze-thaw resistance, and fire resistance was illustrated. Moreover, the effect of binder, chemical admixture, mixing time, vibration, pumping, temperature, and low atmospheric pressure on the parameters of the air-void system were reviewed in detail. In the end, the future researches on this topic are also recommended.